Molecular Docking Approach and Enantioseparation of Hydroxychloroquine by High-Performance Liquid Chromatography using Amylose Tris (3,5-dimethyl phenyl carbamate) as the Chiral Selector - Dadan Hermawan; Salsabil Rahmadina; Irmanto Irmanto; Amin Fatoni; Suwandri Suwandri; Mudasir Mudasir; Hassan Y Aboul-Enein (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
The chiral separation of hydroxychloroquine, an antimalarial drug with one chiral center, has been predicted using molecular docking and was proven using the HPLC method. Docking utilized the PM3 semi-empirical method with specific grid coordinates (X = 19.977, Y = 20.069, and Z = 25.901) and a grid size of (X = 20, Y = 20, and Z = 60), employing a grid spacing of 1,000 Å, an exhaustiveness value of 8, and num_modes of 10. The analysis revealed the enhanced stability of R-hydroxychloroquine within the tris amylose complex, resulting in slower retention and elution rates compared to S-hydroxychloroquine. The HPLC experimental validation demonstrates resolution (Rs = 2.23), successfully achieved by employing amylose tris-based chiral columns. The mobile phase composition employed in this study consisted of acetonitrile:aquabidest: dimethylamine (47:52:1, v/v). Detection was performed at 343 nm, and the optimized HPLC method successfully quantitatively determined hydroxychloroquine in a liquid pharmaceutical sample with a percentage recovery of 98.47%.